Evaluation of Host Community Attitudes to the Development of Social Pathologies Caused by the Development of Tourism in the City of Hamedan - Shahla Kazemipour Sabet; Hossein Rezaii; Hadiseh Ramezanifar (Taḥqīqāt-i Farhangī-i Īrān, 2015)
The subject of the present article is to evaluate the host community attitudes about expanding social pathologies caused by the development of tourism in the city of Hamedan. The survey method (descriptive–analytical) was used in this study and researcher made questionnaire in the form of Likert was used. For this purpose, the entire population was divided into two different groups, including local residents, and shopkeepers who depend on tourism activities. The theoretical framework used in this paper is the Travis Hirschi's social control theory. Also, in this study, stratified random sampling method was used with a combination of male and female, between the ages of 18 and higher, and accordingly, the statistical sample selected on the basis of the Cochran formula is estimated 400 persons. To assess the reliability of research tools, as well as Cronbach's alpha is used, which its coefficient is 0.83. Information collected through questionnaires, after encoding, using the statistical software SPSS, have been analyzed. The results of this study show that tourism in the city of Hamedan partly is developed. The results indicate that, there is a significant relationship between tourism development and the attitudes of respondents to increase social pathologies. With regard to significant level achieved (Sig = 0.000), and with 95 confidence level, it can be said that this relationship is significant. The intensity of the relationship between the two variables is equal to 0.20. The results show that citizens in Hamedan about the negative impacts, and rating of developed social pathologies, have considered the distribution of Anti-cultural items with the average of 3.33 of 5 as a factor of social pathologies with the highest rank, and the spread of gambling with the average of 2.04 of 5 as a factor of social pathologies with the lowest rank.